Credit risk management resource efficiency in the implementation on Basel Accord: a study of Pakistani banking sector. (17th January 2023) - Shah, Syed Alamdar Ali; Fianto, Bayu Arie; Sukmana, Raditya; Herianingrum, Sri
This research endeavours to examine credit risk management (CRM) capabilities for Basel accord implementation in Pakistani banks. The results obtained depict that the banks in Pakistan do not have adequate human resource capabilities for CRM that is affecting their risk performance and Basel accord implementation. This research introduces a new measure of credit risk measurement, which is credit risk weighted assets to credit risk employees ratio. This ratio has been used for measuring capabilities of banks for implementation of Basel Accord. Keeping in view the results it is suggested that further work is required by the banks and the regulators to improve the availability and training of human resources for CRM and ultimately to reap the benefits of Basel Accord implementation.